Some issues on gender and the teaching of geography in secondary schools in Kano state,Nigeria. - Mohammed, Nuratu (American Journal of Humanities and Social Sciences, 2014)
The study examined some issues on gender and the teaching of geography in Nassarwa educational zone in Kano state.Stratified random sampling was used to select 15 schools out of the 34 senior secondary schools in the zone.All the 26 geography teachers in the study area were used as samples.In addition 70 male and female stuents in the sampled schools were also selected as samples.The data collected was analysed using descriptive statistcs.The results of the study show that 85% males and 15% female teach geography in Kano state.Some of the reasons for the disparity according to the teahers :lack of interest (31%),broad nature of the subject (31%).fear of the subject which emantes from the negative perception of the females inadequate infrasructures( 31%)and others7%.It was also found that the lack of interest of the students in addition to the broad nature of the subject and inadequate time usually alloted to it,inadequate qualified teaching staff and lack of infrastuctues are among the problems of teaching geography in secondary schools. This paper therefore recommends the following: The need to make geography more interesting by providing all the necessary infrasructures to that effect. Keywords: Gender, Focus. Group, Patriachy and Development